Food system design for resilient communities – Urban agriculture and sustainable spaces - Stefano Follesa; Martina Corti; Diletta Struzziero; Aurora Piluso (Agathón)
In the post-pandemic society with numerous social challenges, there is an increasing focus on public institutions to provide new services. The 2030 Agenda emphasises the need for sustainable and inclusive development, reducing inequalities in cities. This study focuses on autonomous and resilient urban food systems, analysing Social Design strategies for greater social cohesion. Urban Agriculture promotes environmental awareness and social inclusion by integrating innovative designs and advanced technologies. This urban regeneration approach aims to transform residual urban spaces into community parks dedicated to sharing resources and building connections between people. Through in-depth analysis and the application of new technologies, urban social and environmental sustainability improvements are sought.